SME competitiveness: internationalization of Josefinas to Japan - Monteiro, Mariana Patrícia Silva (2019)
This thesis was developed with the goal of exploring an internationalization strategy of Josefinas to Asia. Therefore, data has been collected regarding the brand’s competitive advantage, followed by the selection of the market that the brand should internationalize to, in this case Japan, and the respective analysis of the Japanese market. Finally, an implementation strategy was suggested, where the entry mode and the resources needed for a successful internationalization of the brand to the Japanese luxury footwear market are approached.